Synthesis and structural studies of ammonium exchanged synthetic analogue of disordered aluminosilicate natrolite - Gavhane, Manjusha J.; Jha, R. K.; Nam, Kyung-Wan; Bhange, Deu S. (Microporous and Mesoporous Materials, 2025)
The current article reports preparation and structural analysis of NH4+ exchanged form of synthetic natrolite zeolite (NH4-natrolite) with disordered structure wherein Si and Al occupies all the tetrahedral (T) sites in the zeolite framework. Structural data is used to gain insight into the structural parameters those influence thermal stability of its proposed H-form. NH4-natrolite is prepared by ion-exchange method from K-natrolite (which was also obtained by ion-exchange with Na-natrolite). Na-natrolite, K-natrolite and NH4-natrolite prepared in this study were tested for their structural, morphological and thermal analysis. Synchrotron X-ray diffraction data was utilized to estimate the crystal structures of hydrated forms of Na-natrolite, K-natrolite and NH4-exchanged natrolites. Thermal analysis of NH4-natrolite revealed that the dehydration is followed by removal of ammonia during calcination. The role of the size (radius) and nature (either divalent or monovalent) of the exchangeable cations present in the channels, the framework chemical content and extent of `T' atom ordering have been collectively discussed and correlated with the structural behaviour of calcined NH4-natrolite to explain its thermal stability in better way.
Keywords: Crystal structure of natrolite; Disordered framework; zeolite